2010
DOI: 10.1210/en.2010-0093
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Differential P450c17 Phosphorylation by cAMP Stimulation and by Starvation Conditions on Enzyme Activities and Androgen Production in NCI-H295R Cells

Abstract: CYP17A1 plays a pivotal role in the biosynthesis of androgens in the adrenals and the gonads. Although this enzyme catalyzes two different reactions on one single active site, its specific activities are regulated independently. Although the 17alpha-hydroxylase activity is rather constant and regulated by gene expression, the 17,20-lyase activity varies significantly with the amount of cofactors or by protein phosphorylation. cAMP increases CYP17A1 expression, P450c17 phosphorylation, and androgen production. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 34 publications
2
50
0
Order By: Relevance
“…Thus dephosphorylation did not degrade P450c17, but diminished 17,20 lyase activity without altering the substrate binding (Zhang et al, 1995). Studies in other laboratories have confirmed that P450c17 phosphorylation increases 17,20 lyase activity (Biason-Lauber et al, 2000;Kempna et al, 2010). When a protein is activated by phosphorylation there is generally an equilibrium between phosphorylation by the kinase and dephosphorylation by a phosphatase (reviewed by Virshup, 2000).…”
Section: Phosphorylation Of P450c17 -Initial Studiesmentioning
confidence: 99%
“…Thus dephosphorylation did not degrade P450c17, but diminished 17,20 lyase activity without altering the substrate binding (Zhang et al, 1995). Studies in other laboratories have confirmed that P450c17 phosphorylation increases 17,20 lyase activity (Biason-Lauber et al, 2000;Kempna et al, 2010). When a protein is activated by phosphorylation there is generally an equilibrium between phosphorylation by the kinase and dephosphorylation by a phosphatase (reviewed by Virshup, 2000).…”
Section: Phosphorylation Of P450c17 -Initial Studiesmentioning
confidence: 99%
“…THE TERM SERUM STARVATION, or simply starvation, as well as serum deprivation, depletion, removal, restriction, withdrawal, and serum limitation have been used to denote various procedures that include growing cells in either reduced serum, serum-free, or serum-and protein-free medium (5,14,16,27,28,34,45,47,50,53,56,57,70). Unfortunately, none of these terms have a well-defined meaning that would unambiguously reflect the actual procedure, and they have all been inconsistently applied to describe different protocols.…”
mentioning
confidence: 99%
“…Alternatively, serum starvation may be carried out in medium with low serum concentration (relative to normal growth medium), typically 0.1-0.5% (6,15,36,47,60), but sometimes as high as 2-5% (13,19,59) or as low as 0.05% (32,58). The time frame for serum starvation is equally varied and can include anything from 15 to 30 min up to several weeks (1,3,4,27,28,49,58,63,72). Moreover, while alternative designations such as serum withdrawal or deprivation are sometimes used synonymously and interchangeably with serum starvation (27,34,56,72), others make a clear distinction based on serum concentration (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The weaker interaction between cytochrome b 5 and P450c17 when 17-OH-Preg is the substrate promotes 17,20 lyase activity by enhancing the interaction of P450c17 with POR (36). Third, serine/threonine (Ser/Thr) phosphorylation, but not tyrosine phosphorylation, of P450c17 will increase 17,20 lyase activity (34,(37)(38)(39)(40). Either maximal Ser/Thr phosphorylation of P450c17 or maximal concentrations of b 5 will maximize 17,20 lyase activity so that adding b 5 to phosphorylated P450c17 elicits no further increase in lyase activity (34), indicating that both factors operate via the same mechanism, presumably optimizing interactions with POR.…”
mentioning
confidence: 99%